Use of Ozonized Perfluorane in Acute Peritonitis - A. M. Golubev; R. M. Ragimov; A. O. Osmanov (Общая реаниматология, 2005)
The properties of ozonized perfluorane were first studied in the treatment of experimental generalized peritonitis. Experiments were conducted on albino noninbred rats. The model of acute peritonitis, proposed by S. S. Remennik, was used. After simulating peritonitis, the animals were intraperitoneally injected saline solution (Series 1), perfluorane (Series 2), ozonized saline solution (Series 3), ozonized perfluorane (Series 4). All the animals intraperitoneally given saline solution died on days 1—7 of the experiment. When ozonized perfluorane was used, all the animals survived. The therapeutic effect of ozonized perfluorane in acute peritonitis was due to the activation of phagocytes and to the antibacterial activity of ozone.